XML pocket reference - Eckstein, Robert (O'Reilly, 2001)
XML, the Extensible Markup Language, is the next-generation markup language for the Web. It provides a more structured (and therefore more powerful) medium than HTML, allowing you to define new document types and stylesheets as needed. Although the generic tags of HTML are sufficient for everyday text, XML gives you a way to add rich, well-defined markup to electronic documents. The XML Pocket Reference is both a handy introduction to XML terminology and syntax, and a quick reference to XML instructions, attributes, entities, and datatypes. Although XML itself is complex, its basic concepts are simple. This small book combines a perfect tutorial for learning the basics of XML with a reference to the XML and XSL specifications. The new edition introduces information on XSLT (Extensible Stylesheet Language Transformations) and Xpath.